2020
DOI: 10.3390/ma13245706
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Silk Sericin from Cocoons of Three Southern African Wild Silk Moths with a Focus on Their Antimicrobial and Antioxidant Properties

Abstract: Silk sericin was extracted from the cocoons of three Southern African wild silk moth species, namely Gonometapostica, G. rufobrunnae (Lepidoptera: Lasiocampidae), and Argema mimosae (Lepidoptera: Saturniidae); these three sericin extracts were analysed to determine the relationship that exists between their chemical structures and their functional properties. The relationship was investigated by utilising several methods that include the determination of the amino acid composition, and characterisation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 45 publications
4
17
1
Order By: Relevance
“…The results that were obtained in antimicrobial assessment of sericin solution are contradictory to some reported studies that demonstrated SS solution showing antimicrobial activity for S. aureus and E. coli [ 44 , 45 , 46 ]. Xue et al [ 47 ] investigated the interaction mechanism of E. coli cells that were treated with SS and SSH for wound healing.…”
Section: Resultscontrasting
confidence: 73%
“…The results that were obtained in antimicrobial assessment of sericin solution are contradictory to some reported studies that demonstrated SS solution showing antimicrobial activity for S. aureus and E. coli [ 44 , 45 , 46 ]. Xue et al [ 47 ] investigated the interaction mechanism of E. coli cells that were treated with SS and SSH for wound healing.…”
Section: Resultscontrasting
confidence: 73%
“…This is due to the fact that the amide I area of the spectrum is the most informative for determining protein secondary structure [45]. The FTIR spectra of amide I are presented in detail as deconvoluted FTIR spectra (Supplementary Figure S2), and the contents of the secondary structures are shown in Figure 4b, revealing that the melaninmodified silks contained more helix and random coil structures and a fewer β-sheets than the control silk, similar to previously reported results [46]. This may be attributed to the formation of hydrogen bonds between melanin and silk fibroins.…”
Section: Ftir Analysissupporting
confidence: 85%
“… 2017 ; Manesa et al. 2020 ). It has been revealed that peptide characteristics, including molecular weight, amino acid sequence and hydrophobicity strongly determine its antioxidant potential (Karamać et al.…”
Section: Discussionmentioning
confidence: 99%